Environmental psychology an introduction - Steg, Linda; Berg, Agnes E. van den; de Groot, Judith I. M. (Wiley-Blackwell, 2012)
"Explores the environment's effects on human wellbeing and behaviour, factors influencing environmental behaviour and ways of encouraging pro-environmental action"-- Provided by publisher.